Loop‐mediated isothermal amplification (LAMP) for the identification of invasive Aedes mosquito species. Issue 3 (8th February 2019) - Schenkel, C. D.; Kamber, T.; Schaffner, F.; Mathis, A.; Silaghi, C.
Abstract: Invasive Aedes mosquito species (Diptera: Culicidae) are of public health concern in Europe because they are either recognized or potential vectors of pathogens. Loop‐mediated isothermal amplification (LAMP) is a rapid and simple method for amplifying DNA with high specificity and efficiency, with the technique having potential for application in the field, including in high‐throughput format. Specific LAMP assays based on rDNA internal transcribed spacers 1 or 2 sequences, considering intraspecies variability at these loci, were developed for Aedes aegypti, Aedes albopictus, Aedes japonicus, Aedes koreicus and the indigenous Aedes geniculatus . No such assays could be developed for Aedes atropalpus and Aedes triseriatus because both loci were too short to serve as target. The assays rely on the clearly visible colour change from violet to sky blue after successful amplification. Sensitivity of egg detection was confirmed with ratios of up to one mosquito egg in 99 other eggs. Simple sample preparation of adults or eggs by mechanical homogenization in water required an additional heat treatment or centrifugation step to avoid non‐specific colour changes. Thus, further technical improvements are needed to render these assays truly field‐applicable, which would greatly facilitate surveillance of these invasive mosquito species and allow for prompt implementation of control measures. Abstract : Loop‐mediated isothermal amplification assays for the invasive container‐breeding mosquitoes Aedes aegypti, Aedes albopictus, Aedes atropalpus, Aedes japonicus, Aedes koreicus, Aedes triseriatus and the indigenous Aedes geniculatus were developed. Intra‐individual and interspecies sequence variability were detected and considered for robust primer design. The sensitivity of the assays was tested, showing that one egg of a species could be detected in 99 other eggs.